(untitled) (Journal of Naval Architecture and Marine Engineering, 2009)
The points of separation of magneto-hydrodynamic mixed convection boundary layer flow along a vertical plate have been investigated. The free stream velocity is considered decreasing exponentially in the stream wise direction. The governing boundary layer equations are transformed into a non-dimensional form and the resulting nonlinear system of partial differential equations are reduced to local non-similar boundary layer equations, which are solved numerically by implicit finite difference method known as Keller box scheme. Here we have focused our attention to find the effects of suction, magnetic field and other relevant physical parameters on the position of boundary layer separation. The numerical results are expressed in terms of local shear stress showing the effects of suction, buoyancy, Prandlt number and magnetic field on the shear stress as well as on the points of separation. Keywords: Separation points, magneto-hydrodynamic, mixed convection, boundary layer, suction, finite difference method, Keller box scheme. Â doi:10.3329/jname.v5i1.1868 Journal of Naval Architecture and Marine Engineering Vol. 5, No.Â 1 (June, 2008) 11-18. Â